Detective Audit: Methodology for Assessing the Business Reliability of a Small and Medium-Sized Business Entity - A. E. Krioni (Учёт. Анализ. Аудит)
The method of private investigations is probably the most appropriate basis for the implementation of independent external control of commercial enterprises. Indeed, if we ignore the analysis of accounting documents that are perhaps the main and only source of financial activity history for the audited company, the remaining problem of forecasting business risk remains the search for unobvious, hidden from the public eyes factors of economic life of the company. In modern crisis conditions such analysis is difficult and requires new approaches for external control.Aims and objectives. The purpose of the work is to develop methodological provisions for the detective form of the layout of the auditing. The offered method is steady in demand among customers of detectives as it opens new opportunities for the honest business executives. This need for the interaction with the private investigation arises from the uncertainty of clients in the auditing opinion, which is one of the consequence of the direct dependence of the external auditor on the audited organization. A detective, on the contrary, is completely independent and free to collect, analyze any information that has to do with the actual financial and economic activities of the company.Methodology. The legal and institutional framework, the instant breakdown of technical equipment area and financial documentation, the interaction and separation of powers controls — these and about sixty more other most important factors are considered in the article, as essential qualitative characteristics affecting the current assessment of the financial and economic activity of the enterprise or firm.Results. The place of the detective auditing in the theory and practice of the auditor activity is specified. External and internal factors that exert a significant influence on the economic and financial activities of the organization are singled out. As a tool for its implementation, the method of factor analysis is proposed. Application area. The results of the research can be applied to the development of external auditing theory and practice.Conclusions. In the conditions of business opacity, detective auditing is a means of choosing future and reliable counterparties for the auditor’s clients.